Just in Time, Just for You: Growing a Peer Learning Program - Miriam Sullivan; Genevieve Franulovich; Sharon Matthews; Andrew Kelly (JANZSSA)
Peer learning programs are well established as an effective approach to improving students’ learning and wellbeing. However, they can be difficult to implement and grow in practice. This paper describes the introduction of a “just-in-time, just-for-me” Peer Skills Advisers program and how it has evolved over the last five years. The peer staff found that the role improved their sense of belonging and employability, but observed that it is challenging to set boundaries with students. The program grew steadily over time as students and staff became more aware of the service, although there is still room for growth in online support.